Effectiveness of intraprocedural dual-phase cone-beam computed tomography in detecting hepatocellular carcinoma and improving treatment outcomes following conventional transarterial chemoembolization. - Youngjong Cho; Sangjoon Lee; Sung-Joon Park (PLoS ONE)
To investigate the effectiveness of intraprocedural dual-phase cone-beam computed tomography (CBCT) in detecting hepatocellular carcinoma (HCC) during conventional transcatheter arterial chemoembolization (TACE) and its effect on improving treatment outcomes. Between November 2018 and November 2019, data from 111 patients with unresectable HCCs (N = 263 lesions) were reviewed retrospectively. All patients had undergone baseline magnetic resonance imaging (MRI) scans within one month prior to the procedure. Both arterial-phase (AP) and delayed-phase CBCT images were acquired during all conventional TACEs. Each HCC detection rate when read by AP-CBCT and when read by dual-phase (DP) CBCT including both AP and delayed phase was compared with that of MRI, and the diagnosis of HCC was based on MRI. Additionally, the follow-up results concerning lipiodol uptake status and tumor response of the lesions detected only by AP-/DP-CBCT were analyzed and compared with MRI-only detected lesions. The overall sensitivity of DP-CBCT (94.7%) was significantly higher than that of AP-CBCT (89.0%) (p = 0.003). In particular, the rate of subcentimeter HCC detection by DP-CBCT was pronounced (91.5% vs. 80.3%) (p = 0.01). Lesions found only by DP-CBCT exhibited positive lipiodol uptake (n = 31/31; 100%) and showed complete or partial responses (n = 24/31; 77.4%) on follow-up CT imaging, while MRI-only detected lesions had less lipiodol uptake (n = 6/14, 42.9%) and complete or partial responses (n = 4/14; 28.6%) (p ≤ 0.001). DP-CBCT imaging during TACE enabled better detection of HCCs than when using AP-CBCT alone, and AP- and DP-CBCT is superior to MRI in detecting chemoembolization-sensitive lesions. This resulted in increased detectability of HCCs and the achievement of better treatment outcomes.